Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
x - wiek syna
y - wiek ojca
x + y = 44 -> y = 44-x
y+4 = 3*(x+4)
44 - x + 4 = 3x +12
4x = 44 + 4 -12
4x = 36 /: 4
x = 9
y = 44 - 9 = 35
wiek syna : 9 lat
wiek ojca: 35 lat
Oznaczymy:
x - wiek syna
y - wiek ojca
x + y = 44
3 * (x + 4) = y + 4
-------------------------------
x + y = 44 ----- y = 44 - x
3 x + 12 = y + 4
-------------------------------
3 x + 12 = 44 - x + 4
3 x + x = 44 + 4 - 12
4 x = 48 - 12
4 x = 36 /: 4
x = 9 - wiek syna
9 + y = 44
y = 44 - 9
y = 35 - wiek ojca